EXISTENTIALISM IN THE WORST PERSON IN THE WORLD MOVIE - Putri Oktavianti; Nina Farlina; Hasnul Insani Djohar (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The difficulty to find meanings of existence and life is a piece of ourselves. Studying existentialism through a movie is suitable for people in general—who in most cases suffer from an existential crisis. This study focuses on the two main protagonists from the movie The Worst Person in the World (2021). To conduct this research, a descriptive qualitative methodology is adopted—in which the two main characters' words and behaviors are the first things to look at while examining existentialism concepts. The data is described based on the existentialism theories of Jean-Paul Sartre, Søren Aabye Kierkegaard, and Albert Camus. As shown in this study, Aksel entered the ethical stage by taking several long-term commitments, whereas Julie had lived her life in both the aesthetic and ethical stages. Due to Aksel's persistent anxiety about death, he chose to rely on ephemeral things to survive. The absurdity in the movie depicted Julie's anxieties. By exploring the similarities and contrasts of Julie and Aksel's existentialism concepts, we can better understand that human beings are unable to avoid the anguish and uncertainty in life. To deal with it is to learn more about ourselves and the most significant thing is to acknowledge a higher authority than oneself—which is God.